1994
DOI: 10.1128/jvi.68.9.5677-5684.1994
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-mouth disease virus leader proteinase: purification of the Lb form and determination of its cleavage site on eIF-4 gamma

Abstract: Many picornaviruses cause a dramatic decrease in the translation of cellular mRNAs in the infected cell, without affecting the translation of their own RNA. Specific proteolysis of protein synthesis initiation factor eIF-4-y occurs during infection with rhinoviruses, enteroviruses, and aphthoviruses, apparently leading to an inability of the ribosomes to bind capped mRNAs. Cleavage of eIF-4-y in human rhinoviruses and enteroviruses is carried out by the viral 2A proteinase; in aphthoviruses (i.e., foot-and-mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(122 citation statements)
references
References 37 publications
(30 reference statements)
5
117
0
Order By: Relevance
“…levels after inhibition of cellular translational function, indicating that 3C pro -induced reduction of PKR protein levels is not totally related to the well-characterized blocking effect of 3C pro on cellular translation. L pro also induces the cleavage of host eIF4G to inhibit host protein synthesis (Kirchweger et al, 1994); however, we observed that over-expression of L pro had no detectable effect on PKR expression (Fig. 4A); it was similar to the observation in the cells treated with a translational inhibitor CHX (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…levels after inhibition of cellular translational function, indicating that 3C pro -induced reduction of PKR protein levels is not totally related to the well-characterized blocking effect of 3C pro on cellular translation. L pro also induces the cleavage of host eIF4G to inhibit host protein synthesis (Kirchweger et al, 1994); however, we observed that over-expression of L pro had no detectable effect on PKR expression (Fig. 4A); it was similar to the observation in the cells treated with a translational inhibitor CHX (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Prior studies identified L pro as a potential virulence factor, with L pro cleaving the host eukaryotic translation initiation factor 4 gamma (eIF4G) that is involved in the translation of cellular and capped mRNA transcripts, thereby prioritizing the translation of viral transcripts [229]. Experiments using an FMDV mutant lacking the L pro domain also implicated the protease in the circumvention of cellular innate immune responses by the inhibition of cellular IFN-α/ β production and associated ISGs, specifically protein kinase R, a cytoplasmic sensor of viral RNA [230][231][232][233][234].…”
Section: Fmdv L Promentioning
confidence: 99%
“…The 2A gene of FMDV is not a functional proteinase, rather cleavage of eIF4G is accomplished by the leader proteinase (L-pro), an alternate papain-like protease encoded at the N-terminus of the viral polyprotein. This proteinase cleaves eIF4GI at a distinct site, seven amino acids upstream of the 2A pro cleavage site, thereby accomplishing the same functional scis-sion of eIF4E-and eIF3-binding domains (Kirchweger et al, 1994). This cleavage reaction has been very well characterized and occurs extremely rapidly, presumably while ribosomes are translating the FMDV polyprotein (Glaser and Skern, 2000).…”
Section: Fmdv L-proteinase Cleaves Eif4gi and Eif4giimentioning
confidence: 99%